A Research Review of the Methodology and Style of Mufti Muhammad Alimuddin’s Works and Translations - Muhammad Zubair; Dr. Muhammad Imran (Journal of Religion and Society, 2025)
This research summary highlights that Mufti Muhammad Aleem al-Din Naqshbandi is among the distinguished contemporary scholars who have adopted a balanced, scholarly, and moderate methodology in the fields of authorship, compilation, and translation. The central focus of his academic contributions is the sound understanding of the Qur’an and Sunnah, the promotion of juristic insight, and providing intellectual and practical guidance to the Muslim Ummah along the path of moderation. His works are characterized by academic integrity, careful use of authentic sources, and deep respect for the interpretive legacy of the great scholars of Islam. The study reveals that the methodology of Mufti Muhammad Aleem al-Din Naqshbandi is fundamentally rooted in a strong reliance on transmitted sources (naqli evidences) accompanied by a balanced and reasoned analytical explanation (aqli reasoning). When addressing any issue, he systematically presents Qur’anic verses, authentic Prophetic traditions, reports of the Companions (رضي الله عنهم), and the opinions of the juristic Imams in a coherent and interconnected manner. A distinctive feature of his approach is his avoidance of unnecessary rigidity or sectarian bias in matters of juristic disagreement. Instead, he guides the reader toward the strongest opinion with academic fairness, thereby cultivating intellectual breadth and moderation.The style of his authored and compiled works is not only scholarly but also reformative and educational. Rather than merely listing legal rulings, he elaborates on their background, underlying wisdom, and practical application in contemporary contexts. This methodological depth makes his writings equally beneficial for students of religious seminaries, scholars, and educated lay readers. His language is clear, idiomatic, and free from ambiguity, which enhances effective communication of complex academic material.In the field of translation, Mufti Muhammad Aleem al-Din Naqshbandi’s methodology is particularly noteworthy. He does not regard translation as a mere literal transfer of words; rather, he prioritizes conceptual and contextual translation to convey the original author’s intent and intellectual spirit accurately to the Urdu readership. To achieve this, he often provides explanatory notes and clarifications to elucidate technical terms, juristic nuances, and subtle scholarly points found in the original Arabic texts. This approach significantly facilitates a deeper and more accurate understanding of the source material for readers unfamiliar with the original language.The research further concludes that Mufti Muhammad Aleem al-Din Naqshbandi’s authored and translated works meet high academic standards while simultaneously addressing the intellectual and practical challenges of the modern era. His methodology represents a harmonious synthesis of tradition and renewal, preserving the classical scholarly heritage while presenting it in a form accessible to the contemporary mind. Consequently, his scholarly contributions constitute a valuable addition to Urdu Islamic literature and provide a solid foundation for future academic research in the fields of Islamic studies, jurisprudence, and religious thought. Keyword: Mufti Alim Al-Din, Services, Classifications and Works, Method and Style, Division, Benefits, Importance